The Influence Of Marketing Mix On Decisions To Purchase Chips At Kreasi Nailah Stores - Darmawan, Rizky; Rahma Ayu, Ade (SEAN Institute, 2024)
The purpose of this research is to find out whether there is an influence of the Marketing Mix on the decision to purchase chips at the Kreasi Nailah store. This research uses a quantitative approach using a questionnaire for data collection. Respondents in this study totaled 80 people. Hypothesis testing and data analysis were carried out using SPSS version 25 software. This research revealed several significant relationships: First, the product has a partially significant influence on purchasing decisions. Second, price has a partially significant influence on purchasing decisions. Third, place has a partially significant influence on purchasing decisions. Fourth, promotions have a partially significant influence on purchasing decisions.